Learning Model on Islamic Religious Education in Improving Student Motivation Andachievement - Sampara Lili; Ana Cahyani Fatima (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
This study aims to assess the shape and Effectiveness of Active Learning model implementation in the field of Islamic religious education studies in improving student achievement motivation and Islamic Elementary School fifth grade Athirah Makassar.This study is a class action (Classroom Action Research) with the kind of collaborative. This research phase follows the model developed by Kemmis and Taggart, namely in the form of a spiral cycleincludes planning, implementation, observation, and reflection. Technique-data collection techniques used are: (1) observation; (2) interview; (3) documentation, and (4) achievement test. Based on the research that has been conducted argued that the application of active learning can increase learning motivation and achievement of students in class V (Al-Mu'min) Islamic Primary School Athirah Makassar on fieldIslamic religious education studies. From the data in the field shows that there is increased motivation of learners whothe original value of the average pre-cycle increased to 69.13 or 63.56 increased by about 5.57% in the first cycle, the second cycle increased to 80.41 or about 16.84%. And in Cycle III are improved Becoming 91.55% or approximately 27.96%. With the increased motivation of learners, then their learning achievement also increased, which had an average value of 63.56 pre-cycle increased to 69.13 or about 5.75% in the first cycle, the second cycle increased to 81, an increase of approximately 17.44%, and in cycle III are improved Becoming 84.63% or approximately 21.7% of the pre-cycle to the third cycle. Active Learners research Based on the results it was concluded that very effective in increasing motivation and learning achievement of students in the field of Islamic religious education studies.